Middle East and North Africa Region Little Data Book, September 2012 - Mottaghi, Lili (World Bank, Washington, DC, 2014)
The data in this book are for 2009 -2011 or the most recent years available, unless otherwise noted in the table or the glossary. This data book presents regional tables which is based on the World Bank's analytical regions and may differ from common geographic usage.